A Study of Factors Affecting Investment Decision of Women Investors: Exploring the Influence of Investment Environment on Women's Investment Decisions (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Indian women are now currently engaging in all spheres of society, including but not limited to theclassroom, the political arena, the media, the scientific community, technological sphere. Women'sparticipation in investing their surplus funds has increased in recent years however, their success indoing so still depends on factors like their risk tolerance, the sway they have with their social circle, andhow difficult it is for them to learn about and gain access to cutting-edge financial tools. The purpose ofthis study is to determine whether aspects of the investment environment in Ghaziabad, Pune, Kolkata,Coimbatore, Bangalore, Hyderabad influence women's investment decisions. Results from a study of2,680 educated women investors in the selected locations show that attachment, information sources,risk tolerance, quality of life, and autonomy all play a role in determining investing strategies. The studyrelies on in-depth interviews with professional women conducted with the aid of a pre-designedquestionnaire. Advisors, distributors, investors, academics will all find this study to be quite helpful.